Partakers or spectators? An analysis of civil society participation in the formulation of environmental policy and legislation in Uganda - Tindifa, S. (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2008.